Publisher Correction: Global-scale evidence for the refractory nature of riverine black carbon. Issue 12 (December 2018) - Coppola, Alysha; Wiedemeier, Daniel; Galy, Valier; Haghipour, Negar; Hanke, Ulrich; Nascimento, Gabriela; Usman, Muhammed; Blattmann, Thomas; Reisser, Moritz; Freymond, Chantal; Zhao, Meixun; Voss, Britta; et al.
In the version of this Article originally published, the units of thex andy axes in Fig. 3a were incorrectly given as 'mg km–2 yr–1 '; the correct units are 'Mg km–2 yr–1 '. These errors have now been corrected in the online versions.